Improved Growth and Yield of Pakchoy(Brassica Rapa L.)with Organic Fertilizer plusVitamin-B1 and Auxin - Bambang Gunawan; M. Ikhsan F; Bambang Wicaksono Hariyadi (Faculty of Agriculture, Merdeka University Surabaya, 2017)
The purpose of this study is to determine the effect of POC Plus concentration on mustard growth and yield. The method used is Group Randomized Design, with 1 (one) factor of POC Plus concentration (Liquinox start)including 8 levels of treatment and 3 replicates. There is significant effect of POC Plus concentration treatment to increase the growth and yield of pakchoy in all parameters of observations compared to the control treatment. The highest gross weight per plant is achieved by treatment L7 at the age of observation 35 days after planting by 338.36%. The highest growth and yield is achieved by treatment L7 by using 17.5 ml per liter of water POC Plus. However, statistically the best value is achieved by treatment L6 with concentration of 15 ml per liter of water POC Plus as there is no significant difference with L7 treatment in all parameters of observations including plant length, leaf number and fresh weight per plant at the age of 35 days after transplanting.